A single injection of kisspeptin‐54 temporarily increases luteinizing hormone pulsatility in healthy women. (20th May 2013) - Jayasena, C. N.; Comninos, A. N.; Veldhuis, J. D.; Misra, S.; Abbara, A.; Izzi‐Engbeaya, C.; Donaldson, M.; Ghatei, M. A.; Bloom, S. R.; Dhillo, W. S.
Summary: Background: Kisspeptin is a novel hypothalamic peptide which stimulates endogenous gonadotrophin releasing hormone (GnRH) secretion. A single subcutaneous bolus injection of kisspeptin‐54 increases circulating luteinizing hormone (LH) levels in women, but its acute effects on LH pulsatility are not known. Aims: To investigate the effects of a single subcutaneous (sc) injection of kisspeptin‐54 administration on LH pulsatility in healthy female volunteers. Methods: Six healthy female adult volunteers underwent 10‐minute blood sampling for serum LH measurement for 8 h during the follicular phase of menstrual cycle. Sc bolus injection of saline or kisspeptin‐54 (0·15, 0·30 or 0·60 nmol/kg) was administered 4 h after commencing the study. A previously described, blinded deconvolution method was used to detect LH pulses. Results: Mean number of LH pulses was increased significantly following 0·30 and 0·60 nmol/kg kisspeptin‐54 when compared with saline (mean increase in number of LH pulses per 4 h, following injection: −0·17 ± 0·54, saline; +2·33 ± 0·56, 0·30 nmol/kg kisspeptin‐54, P < 0·05 vs saline; +2·33 ± 0·80, 0·60 nmol/kg kisspeptin‐54, P < 0·05 vs saline). LH pulse secretory mass increased following injection of 0·60 nmol/kg in five of six subjects, but the mean change in all subjects was non‐significant when compared with saline (mean increase in pulse secretory mass in IU/l following injection: +0·35 ± 0·40, saline; +2·61 ± 1·17, 0·60 nmol/kg kisspeptin‐54, P = 0·10 vs saline). Conclusions: A single injection of kisspeptin‐54 temporarily stimulates the number of LH pulses in healthy women. Further studies are required to investigate the therapeutic potential of kisspeptin‐54 injection to restore LH pulsatility in patients with reproductive disorders caused by impaired GnRH secretion.